Analisis Keuntungan Usaha Pedagang Sayur Di Pasar Pinasungkulan Karombasan Kota Manado (Studi Kasus Pada Pedagang Sayur Sawi Putih, Wortel Dan Kubis) - Givethee, Audina; Kumaat, Ribka Magdalena; Benu, Noortje Marselianie (AGRI-SOSIOEKONOMI, 2023)
This study aims to analyze the profits of vegetable traders in the Pinangsungkulan Market, North Karombasan. The research was carried out for 3 months, from March to May 2020. The research was conducted at the North Karombasan Pinasungkulan Market. This research uses primary data and secondary data. Primary data was obtained through interviews using a questionnaire (questionnaire) to vegetable traders at Pinasungkulan Market, North Karombasan. Secondary data was obtained from books available locally, the internet and accessing articles from various scientific journals. Revenue is obtained from the number of purchases of vegetables or the amount of production multiplied by the number of sales of vegetable traders for one week. The results of the study show that the vegetable traders in the Pinasungkulan Karombasan Market, Wanea District, Manado City can be said to be profitable. The total profits obtained from 15 respondents amounted to IDR 23,949,845 with an average of IDR 1,596,656 for selling vegetables in one week. This income value is quite enough for one week's income, it is possible that it will increase if vegetable buyers increase, especially on holidays which require the local community to buy more vegetables.